Escape to Florence : a novel - Devereaux, Kat (Harper, 2023)
"Moving between the Second World War and the present, an exhilarating debut novel in the vein of Jennifer Robson, Kate Quinn, and Natasha Lester, about two women, decades apart, whose fates converge in Florence, Italy. Only fourteen, Stella Infuriati is the youngest member of her town's resistance network during World War II. Risking torture and death, she relays messages, supplies, and weapons to partisan groups in the Tuscan hills. Her parents have no idea, consumed instead by love and fear for their beloved son, Achille, a courier and unofficial mechanic for a communist partisan brigade. Then, after 1945, Stella seemingly vanishes from the records. Her name and story are overshadowed by the tragic death of her brother-until a young writer arrives in Tuscany in the spring of 2019, uncovering long-buried secrets. Fleeing an emotionally abusive marriage and a lonely life on an isolated estate, Tori MacNair has come to Florence, the beautiful city her grandmother taught her to love, to build a new life. As she digs into her family history with the help of Marco, a handsome lawyer, Tori starts to uncover secrets of the past-truths that stretch back decades, to a young woman who risked everything to save her world ... "--